Dampak Stigma Sosial terhadap Insecurity dan Konsep Diri pada Remaja dengan Keterbatasan Fisik - Lintang Poetri Novitasari; Abrar Surya Negara; Noer Rakhmah Syafara Aurellia; Viona Agustin; Denok Setyawati; Muhammad Farid Ilhamuddin (STKIP Subang, 2026)
This study aims to analyze the impact of social stigma on insecurity and self-concept in adolescents with physical disabilities through a literature review method. Adolescence is the most crucial phase in the formation of identity and self-concept, which is influenced by social acceptance and assessment from the surrounding environment. Adolescents with physical disabilities often experience negative stigma in the form of labeling, discrimination, and social exclusion, which impacts their psychological condition. This study uses a qualitative method with a literature review design through a review of various scientific articles. Data were obtained through searching academic databases and then analyzed using content analysis and inductive thematic analysis. The results of this study indicate that social stigma can have a significant negative impact on adolescents with physical disabilities, then emerging feelings of insecurity, low self-esteem, withdrawal from the surrounding environment and the formation of a negative self-concept. However, several studies also show that support from surrounding people such as family, friends, and the surrounding environment can help adolescents to build resilience, increase self- confidence and a positive self-concept. Therefore, increasing awareness from the community or surrounding environment is essential to reduce stigma and support the psychological well-being of adolescents with physical disabilities.